PERIODONTAL DISEASE AND CANCER: WHAT IS THE RELATIONSHIP? - Fernanda de Araujo Verdant Pereira; Carolina de Assis Pinto Ferreira; Daniela Cia Penoni; Anna Thereza Thomé Leão (Portal de Periódicos da Marinha do Brasil, 2021)
Periodontal disease (PD), characterized by chronic inflammation associated with dysbiosis, has been linked to several pathologies in the human body. Recent studies reveal a strong association between PD and cancer. The objective of this article was to carry out a narrative review of the literature on the relationship between both diseases. A search was performed in the Virtual Health Library (BVS), PubMed and Wiley Online Library databases, with the health descriptors (DECs) in Portuguese: "Doença Periodontal" and "Carcinogênese" and "Neoplasma", and their correspondents in English, "Periodontal Disease" and "Carcinogenesis" and "Neoplasm". The inclusion criteria were complete articles published in English, Portuguese and/or Spanish from 2010 to 2020, resulting in 22 articles. It was found that, although the inflammatory process resulting from PD occurs locally in the oral cavity, the inflammatory cells and their products, the periodontopathogens -- responsible for this inflammation together with the host's immune response -- and the bacterial components can act on the organism in general. Consequences are possible changes in the cell cycle, cell proliferation, apoptosis, immune and inflammatory responses. In addition, periodontal pathogens are able to interact directly with cells in the body and thus stimulate carcinogenesis, tumor progression and/or metastasis. These facts studied in conjunction with epigenetics have revealed a positive association between several cancers and PD. It was concluded that, although some mechanisms involved in the association remain uncertain, epidemiological studies have added a new panorama for the correlation